Atomic transistors beyond Moore's law - Li, Haifeng (Nanyang Technological University, 2023)
This dissertation presents the characterization and fabrication of black phosphorous (BP) field-effect transistors (FETs). Schottky barrier and carrier transport regime at the metal/semiconductor interface is modified by forming a van der Waals heterostructure, which causes the reduction of the contact resistance of the device. Experimental methods include mechanical stripping, PDMS all-dry transfer method, wire bonding, etc. The electrical characteristics of BP-based FETs are characterized by measuring their current-voltage (IV) characteristics with packaged chip carriers and test boxes. By forming a vdW heterostructure at the metal/semiconductor interface, the contact resistance of BP-based FETs can be effectively decreased. BP-based FETs with reduced contact resistance exhibit improved electrical performance, including higher current density and higher transconductance. The scope of the study is limited to reducing contact resistance, and future work may include optimizing parameters such as subthreshold swing. Overall, this study demonstrates the development of high-performance BP-based FETs and opens up new opportunities for their applications in the fields of electronics and optoelectronics.